1981
DOI: 10.1002/cber.19811141116
|View full text |Cite
|
Sign up to set email alerts
|

Au55[P(C6H5)3]12CI6 — ein Goldcluster ungewöhnlicher Größe

Abstract: Die Reduktion von C6H5)3PAuCl mit B2H6 in Benzol ergibt Au9,2[P(C6H5)3]2Cl, das mittels Molmassebestimmungen als Au55[P(C6H5)3]12Cl6 charakterisiert wurde. Ein einfaches Modell, beruhend auf einer Anordnung dichtest gepackter Goldatome, führt zu einem Goldcluster, dessen Aufbau mit der ungewöhnlichen chemischen Zusammensetzung in guter Übereinstimmung ist. Das Mößbauer‐Spektrum der Verbindung zeigt vier Sorten von Goldatomen: einen metallischen Anteil (Au13‐Kern), durch P(C6H5)3‐bzw. Cl‐Liganden Koordinierte A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
321
1
13

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 625 publications
(343 citation statements)
references
References 11 publications
8
321
1
13
Order By: Relevance
“…Diborane can be also utilized as the reducing agent. Reduction of Au(PPh 3 )Cl in benzene gives Au 55 (PPh 3 ) 12 Cl 6 [67], but its single-crystal structure is not available yet.…”
Section: Scheme 5 Examples Of Simple Ligand-exchange Reactionmentioning
confidence: 99%
“…Diborane can be also utilized as the reducing agent. Reduction of Au(PPh 3 )Cl in benzene gives Au 55 (PPh 3 ) 12 Cl 6 [67], but its single-crystal structure is not available yet.…”
Section: Scheme 5 Examples Of Simple Ligand-exchange Reactionmentioning
confidence: 99%
“…For the synthesis of molecular gold clusters typically phosphine gold(I) complexes are reduced with boranes or borohydrides in organic solvents [7,8]. For instance, well-formed crystals of [Au 9 (PPh 3 ) 8 ](NO 3 ) 3 can be obtained reliably by reducing [Au(PPh 3 )NO 3 ] with NaBH 4 in ethanol, followed by purification and crystallization from diluted solutions [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, well-formed crystals of [Au 9 (PPh 3 ) 8 ](NO 3 ) 3 can be obtained reliably by reducing [Au(PPh 3 )NO 3 ] with NaBH 4 in ethanol, followed by purification and crystallization from diluted solutions [9]. The cluster cation [Au 9 (PPh 3 ) 8 ] 3+ can be crystallized in two conformations of the gold polyhedron, the so-called crown structure and the butterfly structure [10,11]. It was found that [Au 9 (PPh 3 ) 8 ](NO 3 ) 3 in its butterfly conformation shows luminescence in the near infrared (NIR) in the solid state, which is advantageous for biomedical imaging [9].…”
Section: Introductionmentioning
confidence: 99%
“…These clusters, also called quantum clusters, are a new class of materials with a definite number of atoms in their core. On the basis of the number of gold atoms present in their core, several clusters such as Au 8 (23)(24)(25)(26), A 11 (27), Au 13 (28), Au 55 (29), etc., have been synthesized. Dickson and co-workers reported strongly photoluminescent silver clusters generated by the irradiation of UV light on oxidized thin films of silver (30).…”
Section: Introductionmentioning
confidence: 99%